2012
DOI: 10.1051/0004-6361/201016334
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the pre-outburst accretion disk in SS Cygni

Abstract: We present results of spectroscopic observations of SS Cygni performed at the 1.5 m telescope of the Loiano Observatory in June 2009, three days before a long outburst. Using results of these observations, we computed Doppler tomograms in three Balmer lines H β , H γ , and H δ . Analyzing the tomograms, we identified gas dynamic features existing in the system. It is shown that in the preoutburst disk a number of shock waves exist. These waves are "hot line" a wave produced by the interaction between the circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…Indeed, our observations are consistent with those by Kononov et al (2012), who found a similar asymmetric emission in the right-hand quadrants. We also find increased emission in the lower-left quadrant of the Hγ map, similar to that found in the Hα tomogram of North et al (2002), as well as the Hγ and Hδ tomograms of Kononov et al (2012). However, there are also differences between our tomograms and those of Kononov et al (2012), confirming their conclusions of changes in the accretion disk between outbursts.…”
Section: Emission Line Featuressupporting
confidence: 94%
“…Indeed, our observations are consistent with those by Kononov et al (2012), who found a similar asymmetric emission in the right-hand quadrants. We also find increased emission in the lower-left quadrant of the Hγ map, similar to that found in the Hα tomogram of North et al (2002), as well as the Hγ and Hδ tomograms of Kononov et al (2012). However, there are also differences between our tomograms and those of Kononov et al (2012), confirming their conclusions of changes in the accretion disk between outbursts.…”
Section: Emission Line Featuressupporting
confidence: 94%
“…IP Peg (eg. Steeghs & Stehle 1999;Morales-Rueda et al 2000), SS Cyg (Steeghs et al 1996;Kononov et al 2012), EX Dra (Joergens et al 2000a,b), U Gem (eg. Groot 2001) and WZ Sge (Baba et al 2002;Steeghs 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, Bisikalo et al (1998) pointed out that in high-mass-transfer rate binaries, the matter can escape the accretion disc and create a halo around the disc. According to their three-dimensional gas-dynamical simulations of accretion flows in a 5.4-h system with typical stellar parameters and a mass-transfer rate of 10 −8 M ⊙ /year, an extended low-velocity region (hereafter called an 'outflow zone') is filled with matter pouring from the disc (Bisikalo et al 2008;Kononov et al 2012). This region is located practically on the opposite side of the disc with respect to the hotspot (labelled as A and B in fig.…”
Section: Accretion Flow Structure In Long-period Nl Systemsmentioning
confidence: 99%